Efektivitas Aplikasi Sabdopalon Dalam Meningkatkan Digital Governance Di Kabupaten Jombang - Chumairoh, Devi Aprilia; Widiyarta, Agus (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2024)
Nowadays technological developments have given birth to many innovations, especially in the government sector. Through Presidential Regulation No. 95 of 2018, it explains that government schemes must be based on the use of digital technology. Public services in village government are often faced with various problems such as queues of applicants. Sabdopalon is an innovation by the Jombang district government in answering this problem, with the Sabdopalon application, online-based services shorten the online service time that the public gets. The aim of the research is to identify the effectiveness of the Sabdopalon application. The method used in the research is descriptive qualitative with an observation and interview approach. The research results show that the Sabdopalon application is considered quite effective for the people of Jombang, people can make requests anywhere and at any time. However, there are some people who still have limited access to facilities such as smartphones and unstable networks. It can be concluded that the quality of public services using digital-based services through the Sabdopalon application has been effective in speeding up requests requested by the public.